Book drop RFID in UMP library - Nor Haslizah, Ramli (2011)
Radio Frequency Identification.(RFID) is evolving as a major technology enabler for identifying and tracking goods and assets around the world.It can help hospitals locate expensive equipment more quickly to improve patient care, pharmaceutical companies to reduce counterfeiting and logistics providers to improve the management of moveable assets.It also promises to enable new efficiencies in the supply chain by tracking goods from the point of manufacture through to the retail point of sale (POS).In addition,it also been apply in library management by improve the current systems in the library.Methodology that be used in this project is a Waterfall Model.This system will be developing using Microsoft Visual Basic 2008. This system makes the borrowing and returning book more practical for the user.